Schematic thinking in attacked one third among players football (A comparative study) (Journal of Hama University, 2022)
The current research included an analytical descriptive study that aimed to identify the level of Schematic thinking in the attacked (one – third) area of football players in Syria, and to identify the level of Schematic thinking in the attacked (one – third) area of players of different positions (defense, midfield, attack) in football, and at the level of Schematic thinking in the attacked (one – third) area between the players of the professional league clubs and the first division clubs, between the players of the men's teams and the players of the youth teams, in addition to identifying the level of Schematic thinking in the attacked (one – third) area between international players and local players. The tactical thinking scale of football players in the attacked (one – third) area which designed by Al-Rawi and Tabeel (2006) was used in the research measurement operation , and the interview tool was also used by asking questions regarding the most important results that were reached to the coaches of the men’s teams in the selected clubs in addition to the coach of the Syrian national team to achieve the goals, and applied to a sample consisting of (64) players and a percentage of (67.36%) of the research community were deliberately selected from football players for youth and men’s teams in each of the clubs (Al-Wahda and Al-Muhafaza) in the governorate of Damascus. The most important results that have been reached: the level of Schematic thinking in the attacked (one – third) area of football players (research sample) in Damascus governorate is good , There were no significant differences in the level of Schematic thinking in the attacked (one – third) area between the players of the different positions (defense, midfield, attack), it was good degree for both defensive and middle players , and for the offensive players the degree was in average , and there is no difference in the level of Schematic thinking in the attacked (one – third) area between the players of the professional league clubs and the first division clubs ( both were good ) .The level of Schematic thinking in the attacked (one – third) area of the players of the men’s teams is higher than the players of the youth teams. There is also a difference in the level of Schematic thinking in the attacked (one – third) area between international players and local players, in favor for international players.